The Synergy of Islam and Local Tradition: A Study of Social Sufism Values Within the Sambelien Tradition in Malangsari, Banyuwangi, Indonesia - Azisi, Ali Mursyid; Syarifudin, Syarifudin; Yazid, Muhammad Afiq bin Mohd (Universitas Islam Negeri Sunan Kalijaga, 2023)
This study delves into the synergy of Islam and local culture, particularly the